2019
DOI: 10.1002/ajmg.a.61396
|View full text |Cite
|
Sign up to set email alerts
|

Adults with Loeys–Dietz syndrome and vascular Ehlers–Danlos syndrome: A cross‐sectional study of health burden perspectives

Abstract: The aim is to study adults with vascular Ehlers-Danlos syndrome (vEDS) and Loeys-Dietz syndrome (LDS) with regard to sociodemographic characteristics, perceived vascular-and multi-organ symptom burdens, and health services utilization. This is a cross-sectional study. In 2018, a postal questionnaire was sent to 71 individuals with genetically verified LDS types 1-4 or vEDS, age ≥ 18 years, recruited through a National Resource Centre for Rare Disorders in Norway. Eighteen patients with vEDS and 34 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 27 publications
(78 reference statements)
1
38
1
1
Order By: Relevance
“…This cross-sectional postal questionnaire survey was part of a larger study of physical functions and psychosocial aspects in adults with HTADs ( 4 , 8 , 13 ). In January 2018, all patients ( n = 70), aged 18 years and older, who had molecularly verified LDS or vEDS and were registered at the TRS National Resource Centre for Rare Disorders ( 14 ) in Norway were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This cross-sectional postal questionnaire survey was part of a larger study of physical functions and psychosocial aspects in adults with HTADs ( 4 , 8 , 13 ). In January 2018, all patients ( n = 70), aged 18 years and older, who had molecularly verified LDS or vEDS and were registered at the TRS National Resource Centre for Rare Disorders ( 14 ) in Norway were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Most individuals with HTADs live with family members who have the same conditions, and many have close relatives who have died at early ages ( 4 ). Persons with HTADs are advised to have regular cardiovascular monitoring, to control their blood pressure with medication, and to schedule prophylactic surgery ( 1 , 2 , 5 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies in children and adolescents with hEDS and Hypermobility Spectrum Disorders (HSD, the current label for patients with joint hypermobility and musculoskeletal complications who do not fulfil the criteria for hEDS) [7] reported on increased fatigue and pain [18], generalized hyperalgesia [21], and improvement of disability after following an outpatient multidisciplinary rehabilitation treatment program [17]. Regarding adults with HCTD, it has been reported that patients with MFS, LDS, EDS and hEDS have persistent fatigue, pain, disability and burden of disease [4][5][6]14,16,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Eye involvement with lens luxation and risk of retinal detachment concerns mainly MFS (Loeys et al, 2010). In LDS, more severe vascular involvement with arterial tortuosity as well as a higher incidence of asthma and gastrointestinal symptoms has been reported (Johansen, Velvin, & Lidal, 2020; Krohg‐Sørensen et al, 2017; MacCarrick et al, 2014). In vEDS, there is a high risk of intestinal (colon) and peripartum uterine rupture and arterial involvement with rupture of branch arteries that might be preceded by aneurysm or dissection—or even occur spontaneously (Byers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%